1.5T versus 3T MRI for targeting subthalamic nucleus for deep brain stimulation. (August 2014) - Cheng, Cheng-Hsin; Huang, Hsing-Ming; Lin, Hung-Lin; Chiou, Shang-Ming
Abstract Background. Accurate stereotactic placement of the electrode into the subthalamic nucleus (STN) is imperative to the therapeutic efficacy of deep brain stimulation (DBS). However, it is not always possible to directly visualize the very small STN using 1.5T MR imaging. Objective. To evaluate whether 3T MR imaging can provide better identification of the STN and clinical outcome than 1.5T MR imaging. Methods. Thirty-nine patients with advanced Parkinson's disease underwent 1.5T (n = 16) or 3T (n = 23) fast spin echo T2-weighted (FSE-T2WI) MR imaging for targeting the STN. A semi-quantitative 3-point scoring system was proposed to rank the clearness of STN contour: Score "0" if non-visible; Score "1" if visible but with blurred margin; and "2" if visible with clear margin. The unified Parkinson's disease rating scale (UPDRS) was also compared before operation and post-operation. Results. The STN score was 2 in all the patients of the 3T group, whereas it was relatively blurred (mean score, 1.19) in the 1.5T group (P < 0.001). The number of microelectrode trajectories (1.2 versus 1.5; P < 0.05) was lower in the 3T group; consequently, the operative time was also less (P < 0.05) as compared with that in the 1.5T group. The outcome of UPDRS motor examination showed no significant difference in two groups. Conclusion. 3T MR imaging is a reliable and more accurate method for direct targeting of the STN for DBS surgery. However, the technique of high-sequence MR imaging may not influence the clinical outcome significantly.